Anion-binding properties of ureidoquinoline and its turn-on fluorescence in the presence of fluoride anions. Issue 28 (8th July 2015) - Kurapati, Sathish; Jo, Yunhee; Hong, Jung-Ho; Kim, Tae-Hyun; Cho, Dong-Gyu
Graphical abstract: Abstract: The anion-binding properties of ureidoquinoline, a derivative of 8-hydroxyquinoline, were investigated. In the presence of anions, ureidoquinoline exhibits turn-on fluorescence rather than its fluorescence being quenched or shifted. These properties are rare for phenol-based sensors. In particular, ureidoquinoline binds to H2 PO4 − and BzO −, while F − binds to ureidoquinoline via its hydrogen bonds when less than 2 equiv of F − are present. With more than 2 equiv of F −, the phenolic OH group of ureidoquinoline is deprotonated. Under such conditions, ureidoquinoline emits intense fluorescence. Under the condition, ureidoquinoline can be used for the detection of fluoride anions under illumination from a laboratory hand-held UV lamp or using a spectrofluorometer.